2022
DOI: 10.1021/acs.jafc.2c01210
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Branched Fatty Acid Esters of Hydroxy Fatty Acids in Teas and Their Potential Sources in Fermented Tea

Abstract: Branched fatty acid ester of hydroxy fatty acid (FAHFA) is a class of natural lipid with important biological functions. In this study, we first profiled natural-origin FAHFAs in different teas using the chemical labeling-assisted liquid chromatography-mass spectrometry method. Consequently, we observed rich molecular diversity of FAHFAs with multiple regioisomers in teas. Additionally, the FAHFA contents had a positive relationship with the tea fermentation degree and a negative relationship with homologous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In line with established research, FAHFAs are a relatively newly discovered class of bioactive lipids with beneficial effects on metabolism and inflammation. 41,42 FAHFAs are still under intensive research, and many of their mechanisms of action and potential therapeutic applications are being explored. Recently, they have gained considerable attention due to their notable association with insulin sensitivity in human subjects.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In line with established research, FAHFAs are a relatively newly discovered class of bioactive lipids with beneficial effects on metabolism and inflammation. 41,42 FAHFAs are still under intensive research, and many of their mechanisms of action and potential therapeutic applications are being explored. Recently, they have gained considerable attention due to their notable association with insulin sensitivity in human subjects.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Additionally, in the HepG2 models, LBT exerted the most potent promotion of the key rate‐limiting enzyme glucokinase (GCK) in the glycolysis process compared to Qingzhuan brick, Pu‐erh, Fu‐brick tea, which was attributed to the high contents of polyphenols, theanine, catechins, tea pigments, and trace elements (Fe and Cu) (Zhu, Yu et al., 2021). Besides, molecular docking indicated that the high content of branched fatty acid ester of hydroxy fatty acid may account for the antidiabetic functions of LBT (Zhu et al., 2022).…”
Section: Bioactivitiesmentioning
confidence: 99%
“…FAHFAs are widely present in nature from yeast to mammals [15][16][17][18][19][20] . A variety of foods such as tea 21 , breast milk 22 , olive oil 23 , and venison 24 are all natural sources of FAHFAs. Furthermore, emerging evidence suggests that human could obtain FAHFAs through dietary intake 1,25 , thus changing the composition and levels of FAHFAs in the body, further improving health.…”
Section: Background and Summarymentioning
confidence: 99%